2021
DOI: 10.3390/ijerph18041491
|View full text |Cite
|
Sign up to set email alerts
|

Designing Age-Friendly Communities: Exploring Qualitative Perspectives on Urban Green Spaces and Ageing in Two Indian Megacities

Abstract: The World Health Organization and the United Nations have increasingly acknowledged the importance of urban green space (UGS) for healthy ageing. However, low- and middle-income countries (LMICs) like India with exponential ageing populations have inadequate UGS. This qualitative study examined the relationships between UGS and healthy ageing in two megacities in India. Participants were recruited using snowball sampling in New Delhi and Chennai and semi-structured interviews were conducted with consenting par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Given the generally low rates of physical activity and higher rates of overweight across all of Indore, it is unsurprising to see that regardless of neighborhood status there appeared to be generally regular presence of park hazards and lower access to parks for adults, and greater access to fast foods and namkeen stores than fresh food stores. In line with the literature from New Delhi and Chennai (Adlakha et al, 2021), slum areas in Indore appeared to have lower access to any parks, and when parks were present there appeared to be some additional issues with safety. Past analysis conducted by the Building Healthy Cities team as part of the Health Promoting Schools initiative in Indore showed that, before the COVID-19 pandemic, only 68% of public schools had a playground and 17% had a sports teacher (Bachani et al, 2020;Bakhtawar, 2021).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Given the generally low rates of physical activity and higher rates of overweight across all of Indore, it is unsurprising to see that regardless of neighborhood status there appeared to be generally regular presence of park hazards and lower access to parks for adults, and greater access to fast foods and namkeen stores than fresh food stores. In line with the literature from New Delhi and Chennai (Adlakha et al, 2021), slum areas in Indore appeared to have lower access to any parks, and when parks were present there appeared to be some additional issues with safety. Past analysis conducted by the Building Healthy Cities team as part of the Health Promoting Schools initiative in Indore showed that, before the COVID-19 pandemic, only 68% of public schools had a playground and 17% had a sports teacher (Bachani et al, 2020;Bakhtawar, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…Research conducted in Mumbai, India found that the quality and accessibility -but not the quantity -of green spaces were associated with neighborhood-level SES, with higher SES neighborhoods having better access to green spaces (Sathyakumar et al, 2019). Qualitative research in New Delhi and Chennai also found that low-income populations reported less access to green spaces, along with lower quality, maintenance, and safety of green spaces (Adlakha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ações como proporcionar áreas verdes em espaços urbanos contribui para a melhoria da saúde, concomitantemente devem ser minimizadas possíveis barreiras, como dificuldade de acesso e falta de instalações amigáveis ao idoso, prevendo superfície antiderrapante e iluminação adequada (29) .…”
Section: Compromisso Com Um Plano De Ação: Cessar O Café Devido Insôn...unclassified
“…A qualitative study examined the relationships between urban green space and healthy aging in two megacities in India. It reports that green spaces are poorly maintained in addition to the lack of safe and age-friendly pedestrian infra- [18]. For their part, Tanyi PL et al also claimed in a research conducted in Nigeria in 2018 that many community settings are not adapted to the older people [6].…”
Section: Spaces and Buildingsmentioning
confidence: 99%